Adaptation of Red Upland Rice Farmers to Climate Change in Semanu District, Gunungkidul Regency - Rahayu Lestari; Wijaya Oki; Cahya Addin Dinar (E3S Web of Conferences)
Farmers face high risks to the success of their production due to climate change, which occurs intensively and continuously, so red upland rice farmers in Semanu District, Gunungkidul Regency, have to adapt. The research aims to describe the adaptation of red upland rice farmers to climate change and determine the factors that influence it. The research location was carried out using purposive sampling. Respondents were defined as red upland rice farmers using a simple random sampling method of 100 farmers. Data analysis techniques include descriptive analysis, score analysis, and binary logistic regression analysis. The research results show that adaptation in farmers aged over 50 years is in the very high category. Meanwhile, farmers under and equal to 50 are included in the moderately adaptive category. Factors influencing red upland rice farmers' adaptation to climate change are land area, age, gender, education, farming experience, number of family members, and distance to market. The implications of this research provide important guidance for policy, namely tailored training for older farmers, educational programs for young farmers, and gender-specific support for women to increase sustainable food security amidst climate change.